Intermittent fasting: A “new” historical strategy for controlling seizures? - Hartman, Adam L. (2012)
In antiquity, fasting was a treatment for epilepsy and a rationale for the ketogenic diet (KD). Preclinical data indicate the KD and intermittent fasting do not share identical anticonvulsant mechanisms. We implemented an intermittent fasting regimen in six children with an incomplete response to a KD. Three patients adhered to the combined intermittent fasting/KD regimen for 2 months and four had transient improvement in seizure control, albeit with some hunger-related adverse reactions.